Isolation of diborenes and their 90°-twisted diradical congeners - Julian Böhnke (Nature Portfolio, 2018)
Attempts to bend and twist multiple bonds in order to alter their reactivities have thus far been met with only modest success. Here, Braunschweig and colleagues isolate double-bond-containing boron-based species and their 90°-twisted diradical analogs, thanks to their stabilization with Lewis basic units.